Can the Obesity Crisis Be Reversed? - Ahima, Rexford S. (Johns Hopkins University Press, 2021)
How can we work together to understand the rise of obesity and reverse its related diseases and societal impacts?Obesity is a complex condition that increases a person's risk for developing diabetes, heart disease, cancer, dementia, and other life-threatening conditions. Contrary to prevailing notions that it results solely from a person's diet and exercise failings, a predisposition to obesity is actually determined by genetics as well as by environmental and socioeconomic factors that lie beyond individual control. In Can the Obesity Crisis Be Reversed?, Dr. Rexford Ahima draws on his extensive laboratory and clinical experiences at top institutions to examine the complicated causes of obesity, as well as the most cutting-edge approaches for prevention and treatment. Ahima looks at how the rising trends of obesity and associated diseases are driving up health care costs. He also offers insight into the widespread suffering that obesity imposes and its disproportionate impacts in minority and underserved communities.Calling for greater societal and community engagement in stemming the obesity crisis, Ahima argues that there is an urgent need to promote healthier foods and environmental infrastructure as well as formal programs that reduce obesity. By understanding and applying fundamental knowledge, Can the Obesity Crisis Be Reversed? makes a convincing case that all of us, working individually and collectively, can help to reverse the obesity crisis.Features• Provides information on the biological pathways that control eating and metabolism• Explains genetic and environmental bases of obesity• Reviews the contributions of diet and physical activity to weight gain while speaking to the folly and dangers of individual blame• Offers practical recommendations for healthy diets, exercise, and lifestyle• Discusses current medical and surgical treatments of obesity• Examines comprehensive societal strategies for obesity preventionJohns Hopkins WavelengthsIn classrooms, field stations, and laboratories in Baltimore and around the world, the Bloomberg Distinguished Professors of Johns Hopkins University are opening the boundaries of our understanding of many of the world's most complex challenges. The Johns Hopkins Wavelengths book series brings readers inside their stories, illustrating how their pioneering discoveries benefit people in their neighborhoods and across the globe in artificial intelligence, cancer research, food systems' environmental impacts, health equity, science diplomacy, and other critical arenas of study. Through these compelling narratives, their insights will spark conversations from dorm rooms to dining rooms to boardrooms.